Increased incidence of colon cancer among individuals younger than 50 years: A 17 years analysis from the cancer registry of the municipality of Milan, Italy. (June 2019) - Russo, A.G; Andreano, A.; Sartore-Bianchi, A.; Mauri, G.; Decarli, A.; Siena, S.
Highlights: Increase in CRC incidence among individuals younger than 50 years of age is a current health issue. Different epidemiological trends might stand for different etiologies of CRC among individuals younger than 50. .This is the first European study, based on long-term and population-based Registry data, exploring trends in CRC incidence in young adults. Differently from US, where rectal cancer incidence is increasing in both genders below 50 years, in our study it is reducing among young women. The study documents a 2.6% annual increase in colon and a 5.3% decrease of rectal cancer incidence, particularly in females. Abstract: Background: Colorectal cancer (CRC) overall incidence has been decreasing in the last decade. However, there is evidence of an increasing frequency of early-onset CRC in young individuals in several countries. The aim of this study is to evaluate the trends of CRC occurrence over 17 years in the municipality of Milan, Italy, focusing on early-onset CRC. Population and methods: This retrospective study was performed using the Cancer Registry of the municipality of Milan, including all cases of CRC diagnosed 1999-2015. Incidence rates were stratified by age and anatomic subsite, and trends over time were measured using the estimated annual percentage change. Age-period-cohort modelling was used to disentangle the different effects. Results: 18, 783 cases of CRC were included. CRC incidence rates among individuals aged 50–60 years declined annually by 3% both in colon and in rectal cancer. Conversely, in adults younger than 50 years, overall CRC occurrence increased annually by 0.7%, with a diverging trend for colon (+2.6%) and rectal (−5.3%) cancer. Among individuals aged 60 years and older, CRC incidence rates increased by 1.0% annually up to 2007, and decrease thereafter by 4% per year, both for colon and rectal cancer. Age-period-cohort models showed a reduction of CRC risk for the cohorts born up to 1979, followed by an increase in younger cohorts. In contrast, rectal cancer among women showed a systematic risk decrease for all birth cohorts. Conclusions: The study highlights increasing incidence of colon cancer in younger subjects and a decrease in incidence rates for rectal cancer in females.